Congregation Shopping During the Pandemic: A Research Note - Higgins, Nicholas J.; Djupe, Paul A. 1971- (2022)
The COVID-19 pandemic provided perhaps the perfect storm to shake up American religion. Congregations closed for a time, the majority offered services online, and people seemed willing to engage with web worship. Moreover, the country was as divided as ever, polarized around the most divisive president in the modern era. In this research note, we focus on data from the middle of the peak of the pandemic (October 2020) to assess the degree to which individuals shopped for new congregations, the degree to which politics and church closures motivated that search, and whether congregational leaving grew during this period. Congregational leaving is perhaps a third greater than normal and shopping appears much higher than normal. Notably, shoppers are not necessarily leavers, and political differences play a role, particularly in the decision to leave among marginal members.
Keywords: political disagreement; Nondenominational; Pandemic; Disaffiliation; congregation leaving; congregation shopping